UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN DITINJAU DARI LAW AS AN ALLOCATIVE SYSTEM - Setiady, Tri; Salidja, Suhaendi (Universitas Wiralodra, 2021)
Many problems concerning food occur in Indonesia, we encountered food circulating in the community who do not heed the provisions on labeling, thus disturbing the public. Food trade expired, the use of dyes that are not intended for food, formalin, foods containing preservatives, or acts of other consequence is very detrimental to the community, it can even threaten the health and safety of human lives, especially for children in general, this cas ususally through of fraud on the food label. label is falsified or misleading adverse effects on human health and development.